In vitro effects of histamine receptor 1 antagonists on proliferation and histamine release in canine neoplastic mast cells. Issue 1 (13th September 2020) - Gamperl, Susanne; Stefanzl, Gabriele; Willmann, Michael; Valent, Peter; Hadzijusufovic, Emir
Abstract: Canine mastocytomas (MCTs) are characterized by rapid proliferation of neoplastic mast cells (MCs) and clinical signs caused by MC‐derived mediators. In dogs suffering from MCT, histamine receptor 1 (HR1) antagonists are frequently used to control mediator‐related clinical symptoms. Previous studies have shown that the HR1 antagonists loratadine and terfenadine exert some growth‐inhibitory effects on neoplastic MCs. We examined whether other HR1 antagonists used in clinical practice (desloratadine, rupatadine, cyproheptadine, dimetindene, diphenhydramine) affect proliferation and survival of neoplastic MCs. Furthermore, we analysed whether these HR1 antagonists counteract IgE‐dependent histamine release from a MC line harbouring a functional IgE‐receptor. HR1 antagonists were applied on two canine MC lines, C2 and NI‐1, and on primary MCs obtained from three MCT samples. The HR1 antagonists desloratadine, rupatadine and cyproheptadine were found to be more potent in decreasing proliferation of C2 and NI‐1 cells when compared with dimetindene and diphenhydramine. Similar effects were seen in primary neoplastic MCs, except for diphenhydramine, which exerted more potent growth‐inhibitory effects than the other HR1 antagonists. Drug‐induced growth‐inhibition in C2 and NI‐1 cells was accompanied by apoptosis. Loratadine, desloratadine and rupatadine also suppressed IgE‐dependent histamine release in NI‐1 cells. However, drug concentrations required to elicit substantial effects on growth or histamine release were relatively high (>10 µM). Therefore, it remains unknown whether these drugs or similar, more potent, HR1‐targeting drugs can suppress growth or activation of canine neoplastic MCs in vivo . Abstract :